FENOMENA PERKEMBANGAN CROWDFUNDING DI INDONESIA - Arief Yuswanto Nugroho; Fatichatur Rachmaniyah (Universitas Kadiri, 2019)
Crowdfunding is an internet-based financial intermediation platform that collects funds from the general public to finance a project or business unit. This study aims to determine the development of crowdfunding in Indonesia, as well as how the development of Indonesian crowdfunding when compared to Asian countries. This Research is a descriptive qualitative study with literature studies. The results of this study can be concluded that the development of crowdfunding platforms in Indonesia is mostly Debt Based. Indonesian society, especially in urban society, they still have not utilized it maximally because there is minimum of literacy related to crowdfunding as alternative funding. The number of crowdfunding in Indonesia compared to other Asian countries, namely India and Malaysia is quite competitive. However, in terms of the percentage level of entrepreneurship, Indonesia is still far behind.Keywords : , , , .